Comparison of progressive maximal swimming tests in elite female water polo players - Tan, F. H. Y.; Polglaze, T.; Dawson, B. (International Journal of Sports Physiology and Performance, 2009)
Purpose: To compare the Multistage Shuttle Swim Test (MSST), Water Polo Intermittent Shuttle Test (WIST) and 5 ´200 m Incremental Swimming Test (IST) responses in elite female water polo players. Methods: Fourteen Australian Women`s National Water Polo Squad members performed the MSST and WIST, and 13 players from a National Water Polo League club performed the IST, MSST and WIST on separate occasions (no goalkeepers were involved). Peak heart rate, blood lactate and ratings of perceived exertion were obtained for all tests. Expired air was collected following all tests for the National League players. Results: The National Squad players scored significantly better (ie, distance covered) in the MSST and WIST than the National League players (effect sizes = 1.60 to 1.79, P < .001). The MSST and WIST scores were significantly correlated (r = .80 to 0.88, P < .001). The MSST scores were significantly correlated with peak oxygen uptake (VO2peak; mL/kg·min) obtained for all tests (r = .58 to 0.59, P < .05). In contrast, there were no significant correlations between the WIST scores and VO2peak obtained for any of the tests (r = .43 to 0.52, P > .05). Differences in VO2peak for the IST, MSST and WIST were nonsignificant (P > .05). Conclusions: The MSST and WIST can discriminate players of different competition standards. The MSST can be used to estimate a player`s aerobic fitness and peak heart rate. The WIST appears to better mimic the intermittent activity pattern of the game, but its application to female players, to assess maximal intermittent endurance swimming performance, requires further evaluation.